Quantum algorithms for attacking hardness assumptions in classical and post‐quantum cryptography - J.‐F. Biasse; X. Bonnetain; E. Kirshanova; A. Schrottenloher; F. Song (IET Information Security)
Abstract In this survey, the authors review the main quantum algorithms for solving the computational problems that serve as hardness assumptions for cryptosystem. To this end, the authors consider both the currently most widely used classically secure cryptosystems, and the most promising candidates for post‐quantum secure cryptosystems. The authors provide details on the cost of the quantum algorithms presented in this survey. The authors furthermore discuss ongoing research directions that can impact quantum cryptanalysis in the future.